(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
The research principle has always enriched practical pedagogical activity. So I, having a certain experience in teaching and educational work, decided to analyze and summarize my observations over 20 years. During this period of time, various theories of learning arose, developed and became leading. Nowadays, a system-activity approach to learning allows you to look at the learning process from the perspective of a student, in order not only to create optimal conditions for learning activities, but also to help him become an active, responsible and independent participant in this process.